A CLINICAL STUDY TO EVALUATE ANTI-HYPERLIPIDEMIC EFFECT OF TGL COMPOUND IN DYSLIPIDEMIA VIS-A-VIS MEDODUSHTI (International Journal of Ayurveda and Pharma Research, 2016)
Dyslipidemia is a biochemical derangement found in number of disorders like Diabetes mellitus, Hypertension, Hypothyroidism etc. Dyslipidemia is an important risk factor for atherosclerosis, coronary artery disease and cerebrovascular disease. Epidemiological studies predict that for each 1% reduction in level of LDL-C there is 1% to 1.5% reduction in the risk of major cardiovascular events. Fewer than one half of patients in the United States discharged from the hospital with proven coronary disease receive treatment for Dyslipidemia given the proof that treating Dyslipidemia brings major benefits. Thusglobal views emphasize the need for early; effective interventions against the Atherogenic Dyslipidemia associated with Diabetic and Non-Diabetic cases and with metabolic syndrome to reduce the risk of premature cardiovascular diseases. In Ayurveda, it can be better correlated with Medodushti which is a functional condition and just a precursor stage of Medoroga and can be easily reversible by effective regimen. A single blind Study was carried out in OPD and IPD patients of Kayachikitsa department of Rishikul Campus, Haridwar for 90 days. Total 20 patients were registered for the trial and treated with TGL compound (Self-formulated drug). All the concerned approvals were obtained and data was analyzed under statistical parameters. A significantly reduction of cholesterol level, Triglycerides, VLDL, CHO/HDL Ratio and highly significant reduction of LDL and LDL/HDL Ratio was found. This research also proved the major role of Agni and Ama in pathogenesis of Dyslipidemia, and all the drugs having Dipana, Pachana, Ama nashaka, Kapha-Medohara, Rasayana and Srotoshodhaks quality will be highly effective.